Evaluation of social life-cycle performance of buildings : theoretical framework and impact assessment approach - Liu, Siyu (2020)
Recognizing the importance of building-specific social impact assessment tools to the achievement of social sustainability of building projects, this study developed a methodological framework for social life cycle assessment of buildings through stakeholder-based approach, which includes the following four parts. (1) An assessment framework was proposed considering four stakeholders, including worker, occupant, local community and society, and impact subcategories associated with different social concerns; (2) Indicators were selected for each subcategory based on the assessment objective and data availability. They were categorized into three groups, including quantitative indicators in generic analysis, as well as quantitative and semi-quantitative indicators in site-specific analysis, and corresponding scoring method were provided; (3) Weights among impact subcategories were generated through questionnaire survey based on analytic hierarchy process method, and weights among life-cycle phases were determined considering the possibility to place control as well as level of concern of construction practitioners; (4) The proposed method was applied to a case study comparing two buildings with different construction methods, namely prefabricated prefinished volumetric construction (PPVC) project and semi-prefabrication project. The result suggests that PPVC project outperforms semi-prefabrication one in terms of life-cycle social performance. This is mainly caused by its capability to protect worker's health and safety as well as its contribution to technology development.